The Protection of The Core Labour Rights of Internal Migrant Workers: The Case of The Internally Displaced Workers (Idws) From the English-Speaking Regions of Cameroon - Akamin Asonga Patrick (Periodica Journal, 2022)
With the advent of the socio-political crisis roughing the Englishspeaking regions of Cameroon since 2016, many workers have fled these regions for their safety and better employment opportunities in other relatively stable regions of the country
Keywords: Protection; Core Labour Rights; Internal Migrant Workers; Cameroon